Business communication in Web 2.0. Strategies for an effective management of corporate reputation - Cristina Pérez Sampol; José María Gómez-Zorilla Amate; Jorge Marco Blanco (Centro de Estudios Financieros, 2015)
CEOs must face a new economic cycle known as the «reputation economy». In this context, it is particularly important the proper management of corporate reputation and brand image. To this purpose, the essential key used by most of the companies is the on-line communication, reached through the development of Web 2.0 and its new tools (such as social media), which help companies to attract the attention of the stakeholders and to interact with them. It is important that company executives should try to adapt the company's strategies to this new economic environment in order to be competitive, so they must pay especial attention in the developing of the on-line communications strategy. It is highly recommended that this strategy rules under the seven pillars of corporate communication, which are distinctiveness, integration, ongoing, social use, user friendly, exhaustive, and concrete. To these seven pillars, it is recommended to add a new pillar: the measurement.